Relationship between outrigger position and external columns size in minimizing building response to wind - Muyideen Oladimeji, Abdulkareem (2010)
This research presents the relationship between the position of outrigger and the size of the external columns in minimizing the building responses to wind. Outrigger system has been one of the many structural systems in tall buildings used to reduce the building responses to wind load. The study on the usage of this system has been given little or no attention to the effect of the size of the external columns to the optimum position of outrigger. This research involves the position of the outrigger being varied and the responses: displacement and acceleration being computed. The procedure is repeated for each different size of the external columns. This analysis is carried out with the use of structural analysis computer software to determine the natural frequency of the building and Excel spreadsheet to determine the responses. The observations from the analysis will provide the conclusion on the relationship between the size of the external columns and the outrigger location with respect to the building response to wind.